High Sulfur Isotope Fractionation Associated with Anaerobic Oxidation of Methane in a Low-Sulfate, Iron-Rich Environment - Weber, Hannah S.; Thamdrup, Bo; Habicht, Kirsten S. (Frontiers in Earth Science, 2016)
Sulfur isotope signatures provide key information for the study of microbial activity in modern systems and the evolution of the Earth surface redox system. Microbial sulfate reducers shift sulfur isotope distributions by discriminating against heavier isotopes. This discrimination is strain-specific and often suppressed at sulfate concentrations in the lower micromolar range that are typical to freshwater systems and inferred for ancient oceans. Anaerobic oxidation of methane (AOM) is a sulfate-reducing microbial process with a strong impact on global sulfur cycling in modern habitats and potentially in the geological past, but its impact on sulfur isotope signatures is poorly understood, especially in low sulfate environments. We investigated sulfur cycling and 34S fractionation in a low-sulfate freshwater sediment with biogeochemical conditions analogous to Early Earth environments. The zone of highest AOM activity was associated in situ with a zone of strong 34S depletions in the pool of reduced sulfur species, indicating a coupling of sulfate reduction and AOM at sulfate concentrations < 50 µmol L-1. In slurry incubations of AOM-active sediment, the addition of methane stimulated sulfate reduction and induced a bulk sulfur isotope effect of ~29 ‰. Our results imply that sulfur isotope signatures may be strongly impacted by AOM even at sulfate concentrations two orders of magnitude lower than at present oceanic levels. Therefore, we suggest that sulfur isotope fractionation during AOM must be considered when interpreting 34S signatures in modern and ancient environment.